Medical assessment in the age of digitalisation - Egarter, Saskia; Mutschler, Anna; Tekian, Ara; Norcini, John; Brass, Konstantin (BMC medical education, 2020)
Digital assessment is becoming more and more popular within medical education. To analyse the dimensions of this digital trend, we investigated how exam questions (items) are created and designed for use in digital medical assessments in Germany. Thus, we want to explore whether different types of media are used for item creation and if a digital trend in medical assessment can be observed.
Gesehen am 29.04.2020